X-band spanar antenna for heart rate monitoring system - Azman, Hazwani (2016)
The demands of Heart rate Monitoring Systems are getting more extensive rapidly in wireless communication application subjects as an important role in modem life for all practical purposes. The early stage of the system was heavy, bulky and costly, but the latest technology in wireless systems is smaller and cheaper. The touch-less technique or contact-less technique heart monitoring using microwave Doppler radar has been given more attention in the activities of detection of cardio-pulmonary since the 1970's. The antenna has become a critical attention in radar and space communication application since the radio link was first built in 1886 by Hertz, whereby the antenna had the function to allow people to stay connected and informed with each other. Due to the increase in demand of the detection monitoring system, Spanar Antenna for the Heart rate Monitoring System is introduced at X-Band frequency. The proposed antenna is designed 20.835mm x 8.9mm to operate at 1 OGHz, which suggested return loss, S 11 less than -1 OdB and gain, G more than 3dB. The elements of antenna structure are referred from basic ice-cream cone, where the slit shape is added for a good antenna performance. The proposed antenna is simulated with Heart rate Monitoring System configuration at 1 Om distance with 10.002dBm minimum input power before implementation process. The elements of system configuration are referred from continuous-wave radar transceiver and homodyne receiver for a good system performance. A continuous-wave radar transceiver conversion has a simple topology. The homodyne or direct conversion receiver has simplicity, low power consumption and inexpensive.